PENGARUH PENGGUNAAN MEDIA KOMIK BERBASIS PIXTON TERHADAP HASIL BELAJAR PPKn SISWA KELAS IV SD NEGERI 227 PALEMBANG - Agus Sentiase; Rury Rizhardi; Ida Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to determine the effect of using Pixton-based comic media on the learning outcomes of Civic Education (PPKn) among fourth-grade students of SD Negeri 227 Palembang. This research employed a quantitative approach with a pretest-posttest control group design. The sample consisted of 66 students, divided into 33 students of class IV A as the experimental group and 33 students of class IV B as the control group. The research instrument was a learning achievement test administered before (pretest) and after (posttest) the treatment. The experimental class was taught using Pixton-based comic media, while the control class was taught using conventional lecture methods. The results showed a significant difference between the posttest mean score of the experimental class (87.88) and the control class (48.79). The hypothesis test using an independent sample t-test obtained a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the use of Pixton-based comic media has a positive and significant effect on improving students’ Civic Education learning outcomes. This media helps students better understand abstract material, increases motivation, and creates a more engaging and enjoyable learning atmosphere.